2021
DOI: 10.3892/ijo.2021.5228
|View full text |Cite
|
Sign up to set email alerts
|

QPCT regulation by CTCF leads to sunitinib resistance in renal cell carcinoma by promoting angiogenesis

Abstract: Sunitinib is widely used as a first-line treatment for advanced renal cell carcinoma (RCC). However, a number of patients with RCC who receive sunitinib develop drug resistance; and the biological mechanisms involved in resistance to sunitinib remain unclear. It has previously been suggested that the protein glutaminyl-peptide cyclotransferase (QPCT) is closely related to sunitinib resistance in RCC. Thus, in the present study, in order to further examine the molecular mechanisms responsible for sunitinib resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Overexpression of MTDH is noted in aggressive BC subsets, such as triplenegative BC and HER2-overexpressed tumors (37). QPCT, a secreted protein implicated in the biosynthesis of pyroglutamyl peptides, is found to contribute to angiogenesis (38). Our preceding experiment suggested that MTDH and QPCT were intensively expressed in local advanced breast tumors and positively correlated with poor disease-free survival.…”
Section: Discussionmentioning
confidence: 95%
“…Overexpression of MTDH is noted in aggressive BC subsets, such as triplenegative BC and HER2-overexpressed tumors (37). QPCT, a secreted protein implicated in the biosynthesis of pyroglutamyl peptides, is found to contribute to angiogenesis (38). Our preceding experiment suggested that MTDH and QPCT were intensively expressed in local advanced breast tumors and positively correlated with poor disease-free survival.…”
Section: Discussionmentioning
confidence: 95%
“…The regulation function of QPCTL of monocyte infiltration under inflammatory conditions had been demonstrated a long time ago ( 37 ). In renal cell carcinoma, the high expression of QPCTL leads to sunitinib resistance by promoting angiogenesis ( 38 ). In chronic kidney disease, chronic treatment with QPCTL inhibitor PQ529 is a novel and effective approach for glomerulonephritis ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glutaminyl‐peptide cyclotransferase (QPCT) is closely related to sunitinib resistance through high‐throughput sequencing (Zhao et al, 2021). The expression of QPCT increased in the sunitinib‐nonresponsive renal cell carcinoma tissues and plasma, and renal cell carcinoma patients with a high QPCT expression have a poor response to sunitinib.…”
Section: Molecular Mechanisms Of Sunitinib Resistancementioning
confidence: 99%